Improved forages for sustainable agriculture: Recommendations for Ethiopia - Mulatu, Kalkidan Ayele; Notenbaert, An; Gizachew Raji, Shimelis; Asmare, Bimrew; Wickander, Niklas; Mwendia, Solomon; Dörch, Peter; Abera, Wuletawu; Brophy, Caroline; Thunes, Karl; Jørgensen, Marit (2024)
This policy brief highlights the significant potential of improved forages, specifically perennial grass-legume mixtures, in addressing key agricultural challenges in Ethiopia, including feed shortages, land degradation, and climate change impacts. Improved forages can enhance livestock productivity, restore soil health, and foster climate resilience. Their benefits extend to healthier livestock, better farmer livelihoods, land restoration, and sustainable agricultural practices, helping to mitigate soil degradation and promote long-term productivity.